Incipient Separation for Hypersonic Shock Wave/Turbulent Boundary Layer Interaction - Haodong WANG; Bowen ZHU; Lin BAO (气体物理)
Shock/turbulent boundary layer interaction (STBLI) is a prevalent and complex flow phenomenon in the aerospace sector that significantly impacts the aerodynamic performance of vehicles. This study investigated the incipient separation conditions of a hypersonic oblique shock wave impinging on a turbulent boundary layer over a flat plate through theoretical analysis and numerical simulations. An explicit predictive formula based on hypersonic similarity parameters and turbulence viscous interference parameters was proposed for forecasting incipient separation in flat plate STBLI. The research considered parameters such as Mach number, Reynolds number, and wall temperature ratio by conducting a series of numerical simulations. The results indicate that the proposed incipient separation criterion demonstrates good applicability across a considerable range of parameters. Further analysis reveals that the Mach number and Reynolds number have a pronounced effect on incipient separation, whereas the wall temperature ratio in the cold wall regime exhibits a minimal impact. These findings and analysis contribute to a deeper understanding of shock-induced separation phenomena in hypersonic flows and facilitate the subsequent prediction of separation scales in STBLI.